THE EFFECTIVENESS OF ONLINE LEARNING BY USING ZOOM APPLICATION (Karya Ilmiah Mahasiswa (KIMA), 2023)
This study aims to discuss how effective online learning is using the zoom application during the covid-19 pandemic is and how the obstacles faced by the students in using the zoom Application as a learning instrument.  In this study, the data collection techniques used were observation, questionnaires, and interviews, which consist of ten statements about the perception of online learning using various applications, especially the zoom application. The ources of data in this study were taken by an English teacher and thirty students of SMP Kartika XX-2 Makassar. The research instruments were onnobservation and the research herself with the approach of a qualitative descriptive design. Data analysis technique used three steps, namely: the data reduction, data display, and conclusion verification. Then the resuls show that teachers give a sensitive perception of online English learning, the process of learning English learning cannot make the English language process more effective in achieving learning objectives. Students also give thee positive perception of offline English learning. Furthermore online English learning can foster students’ independent learning attitudes, but they find obstacles in the implementation of online English learning cannot be done up.